Delia Grace on why keeping more animals brings more health risks to human populations - International Livestock Research Institute (International Livestock Research Institute, 2011)
Increasing numbers of domestic livestock and more resource-intensive production methods are encouraging animal epidemics around the world, a problem that is particularly acute in developing countries, where livestock diseases present a growing threat to the food security of already vulnerable populations. Delia Grace, a scientist with the International Livestock Research Institute, was interviewed by the BBC's Farming Today program.